Excel 2019 basics : a quick and easy guide to boosting your productivity with Excel - George, Nathan ([Place of publication not identifed] : [publisher not identified], 2019)
Excel 2019 Basics covers all you need to quickly get up to speed with creating spreadsheets to provide solutions for your data. If you are new to Excel and the thought of spreadsheets makes your head spin, then you've come to the right place. This book will hold your hand through a step-by-step process in becoming skilled with Excel. If you already have some Excel skills and you want to skill-up on more advanced topics like functions, Excel tables, pivot tables, and charts, then you've also come to the right place. Excel 2019 Basics goes beyond introduction topics and covers topics like functions, Excel tables, and analysing your data with charts. The aim of this book is to guide you from beginner to being skilled with Excel within a few short hours.
Introduction -- 1. Getting started with Excel -- 2. Entering and Editing Data -- 3. Design and Organise workbooks -- 4. Organizing your data -- 5. Formatting Cells -- 6. carrying out Calculations with formulas -- 7. Creating Data validation Rules -- 8. Named ranges -- 9. Working with functions -- 10. Working with Tables -- 11. Introduction to pivot tables -- 12. Creating Charts -- 13. Printing your worksheet -- 14. Securing Your Workbook.
Includes index.
Keywords: MICROSOFT EXCEL (COMPUTER FILE)